Impact of buriti flour addition in gluten-free cookie (Research, Society and Development, 2020)
Currently, in order to increase the supply of products for celiacs, new raw materials have been added in the biscuit formulations. Therefore, buriti flour (BF) is a viable alternative for the preparation of these products. The study aimed to prepare gluten-free cookies containing BF. For that, four formulations were produced containing 0%, 2.5%; 5.0% and 7.5% BF. The analysis of technological characteristics, color and sensory evaluation were performed. The BF provided higher (p